Exemplary Parenting as a Method of Family Education: An Exegesis Approach to QS. As-Shaff [61]:2 - Abu Rizki, Ahmad; Haedar, Andi Syarifah Farafebrina; Firman, Firman (Proceeding of International Conference on Islamic Education (ICIED), 2025)
This study examines exemplary parenting as a method of family education based on the Qur’anic perspective through an exegesis of Q.S. As-Shaff [61]: 2. Unlike previous studies that generally discuss role modeling (uswah ḥasanah) in Islamic education, this research specifically analyzes exemplary parenting by grounding it in the Qur’an’s explicit critique of inconsistency between speech and action. This clarifies the research gap by showing what earlier studies did not address and establishes the novelty of this study. Using a qualitative library research design, this study analyzes primary sources, including classical and contemporary tafsir such as Tafsir al-Tabari, Tafsir Ibn Kathir, Tafsir al-Maraghi, and Tafsir al-Misbah, along with a thematic-exegetical analytical approach and secondary literature on Islamic family education. The findings indicate that exemplary parenting serves as the study’s theoretical contribution by linking Qur’anic integrity principles with contemporary family education, showing that parental consistency significantly strengthens the internalization of values, while inconsistencies may lead to moral dissonance in children. The study concludes that exemplary parenting integrates moral, spiritual, and social dimensions and holds practical significance for strengthening contemporary family education amid digital-era challenges. This highlights the study’s conceptual and practical implications and reinforces parents’ roles as primary moral exemplars.